Macro-regional strategy for the transformation of the Peruvian productive system: 2011-2021 - Aranaga Manrique, David (2010)
The regions are far from sustainable economic development, as they respond to a primary-export model of outward growth. Despite a decade of decentralization, there has been no budgetary reform with a regional-national vision. The advancement of the macro-regional alternative requires a modern, participatory, planning and decentralized State that applies an inside-out model.